Building resilience knowledge for sustainable development: Insights from development studies - Albert Sanghoon Park (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
This paper explores how the concept of resilience has been used in development studies. Set amidst the rise of resilience in sustainable development, it offers insights for scholars and policy-makers, alike. Sampling 419 resilience-oriented journal articles from 2017-22, it uses Kuhnian paradigms to analyse development knowledge production. This produces three key findings. First is the absence of a coherent resilience paradigm (with shared definitions, problems, and methods) in development studies. Second is its use, instead, by pre-existing paradigms as a theoretical add-on to better address complexity and/or as a new buzzword to repackage prior arguments. Third are latent possibilities for resilience as both a rallying call and siren song in sustainable development. Here, resilience discourses open vital space for development cooperation and climate action. However, its outcomes will depend on whether we can first understand precisely what we talk about when we talk about resilience.
Keywords: I15; I18; O20; Q01; Q56; R11; R58; 330; resilience; sustainable development; development policy; development studies; Kuhnian paradigms; politics of knowledge